EMPLOYMENT AND ECONOMIC EMPOWERMENT OF WOMEN IN COASTAL COMMUNITIES IN THOOTHUKUDI DISTRICT - Mary, K. Myclin; R. Maruthakutti (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Traditional or Modern society women discriminated by men in all the activities of the society. The empowerment of women means the development activities of women to be economically independent, self-reliant, self-esteem and also women should participate in the process of decision making whether it is in social participation, political participation, economic participation, access to education, etc. Traditionally the society followed the patriarchy society that is fully based on male dominated society. This paper seeks to identify the employment of women emancipation them in economic empowerment of their life. The study carried out 244 women among coastal communities in the Thoothukudi District. The data collected by primary data through interview schedule and the married women was the respondent of this study. The study finds out that employment is very important for every woman to stand independently in financial throughout their life. Nearly one fourth (22.1%) of the respondents have employed because of their spouse irresponsibility’s in their family. Due to this reason the woman can easily access the any job in their life to fulfill their family basic needs.